Muslimansko prebivalstvo Sandžaka - Fišer, Jakob (Etnolog. Nova vrsta (Ljubljana), 2013)
The article addresses the issue of national identification among the Muslim population of Sandžak. It focuses on a comparative analysis of such identification among the inhabitants of the Serbian and Montenegrin parts of the region. The core of this analysis derives from the results of a field research in Sandžak carried out between March and May 2012. In this analysis we clearly observed differences between the two countries, and the second partof the article therefore attempts to theoretically explain them. In doing so the issue of national identity in Sandžak is treated as part of the wider issues of the development of national identities in general.
Keywords: ethnology; etnologija; ljudsko življenje; Serbs; Srbi; Črnogorci; Sandžak; nacionalna identiteta; ljudska verovanja; Muslim; muslimani; zgodovinski pregledi